A patatin-like protein with galactolipase activity is induced by drought stress in Vigna unguiculata leaves. (December 2000) - Matos, A. R.; d'Arcy-Lameta, A.; França, M.; Zuily-Fodil, Y.; Pham-Thi, A. T.
Abstract : This paper reports the cloning of a cDNA ( Vupat 1 ) expressed in Vigna unguiculata leaves coding for a protein with 48% sequence homology to patatin, the major protein from potato tuber which has lipolytic acylhydrolase activity. Two cultivars differing in drought tolerance were ex-amined in Northern-blot analyses. Expression of Vupat 1 is stimulated by drought stress, especially in the drought-sensitive cultivar. Vupat 1 was expressed in the baculovirus system as a fusion protein secreted in the culture medium. The recombinant protein displays lipolytic activity towards monogalactosyldiacylglycerol, digalactosyldiacylglycerol and sulphoquinovosyldiacylglycerols.